Prevalence of mastitis in goats from Ladang Angkat UPM and its relationship with selected risk factors - Wan Ishak, Wan Mohd Sukri (2015)
This study was carried out to determine the prevalence of clinical and subclinical mastitis in goat farms of Ladang Angkat UPM, pathogens in milk, and to determine the relationship between selected risk factors and mastitis. A total of 158 milk samples from 80 goats of eight farms were collected aseptically. Clinical mastitis was assessed based on abnormalities of the udder and milk, subclinical mastitis was tested on-site using the California Mastitis Test (CMT), bacteriological culture for identification of pathogens, and Kirby-Bauer disk diffusion method for the antibiogram. The selected farm risk factors for mastitis investigated using questionnaire. Overall prevalence of mastitis at halves level was 49% (clinical, 5%; and subclinical, 44%). Of the 70 milk culture positive, coagulase negative staphylococci (CNS) were predominant, 73% (n=51). Bacillus sp., 11% (n=8); Streptococcus agalactiae, 7% (n=5); Streptococcus viridans, 7% (n=5); Staphylococcus aureus, 4% (n=3); Staphylococcus hyicus, 4% (n=2); Staphylococcus intermedius, 3% (n=2); Enterococci, 3% (n=2); and Klebsiella pneumoniae, 3% (n=2). The least isolated pathogens (1% each) were Escherichia coli, Acinetobacter iwoffii, Achromobacter sp., Streptococcus dysagalactiae, Proteus mirabilis, and Pseudomonas fluorescence. Thirty Staphylococcus sp. isolates tested for antibiotic resistance showed highest resistance against penicillin (37%) and highest susceptibility to streptomycin (97%). There was significant association between mastitis and teat lesions and feed supplement (p<0.05). It is suggested that goat farmers of Ladang Angkat UPM to institute preventive and control measures for mastitis to minimize prevalence thus to reduce losses due to this condition.